A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
Select one of the factors of x*2y*3 − 11x*2y + 6y*2 − 66.
a. (x*2y + 6)
b. (x*2y − 6)
c. (y*2 + 11)
d. (y − 3)
anonymous
 one year ago
Select one of the factors of x*2y*3 − 11x*2y + 6y*2 − 66. a. (x*2y + 6) b. (x*2y − 6) c. (y*2 + 11) d. (y − 3)

This Question is Closed

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0heres what i had to go thurgh

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0(x^2)(y^3) – 11(x^2)(y) + 6(y^2) – 66 = 0 (x^2)(y^3)  11(x^2)(y) + 6(y^2) = 66 Factor a "y" out of the left side. y[(x^2)(y^2)  11(x^2) + 6y)] = 66 (x^2)(y^2)  11(x^2) + 6y = 66 / y Now put the 6y on the other side. (x^2)(y^2)  11(x^2) = (66 / y)  6y Factor, now, the x^2 on the left side. (x^2)[y^2  11] = (66 / y)  6y I would advise, now, finding a common denominator for the right side so that you can get rid of the fraction. (66 / y)  6y = (66 / y)  ((6y^2) / y) = (66  6y^2) / y So now you have: (x^2)[y^2  11] = (66  6y^2) / y Divide the y^2  11 part off to the right side: x^2 = (66  6y^2) / [y * (y^2  11)] Notice how you can factor out a 6 in the numerator. x^2 = [6(11  y^2)] / [y * (y^2  11)] Factor a negative off of the top so that you can divide out the (y^2  11). x^2 = [6(y^2  11)] / [y * (y^2  11)] x^2 = 6 / y Put everything on one side so that the equation = 0. (x^2)(y) = 6 (x^2)(y) + 6 = 0. The answer is A.
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.